Debating Wholesale Telecommunications Reforms - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2018)
Papers in the June 2018 issue of the Journal cover what to do with the National Broadband Network when the rollout is completed, Unmanned Aerial Vehicle communications, energy efficient mobile ad-hoc network communications and a historical look at the Black Mountain Tower in Canberra. With the completion of the National Broadband Network rollout in coming years, there will be an opportunity for substantive wholesale telecommunications reforms to occur that will shape the telecommunications industry for decades to come. Central to this debate is the future of the National Broadband Network: it is important that this debate commence now, so that there will be time to explore the options and for the telecommunications industry, government, business and consumers to come to a consensus on what should happen next and what the expected outcomes of the wholesale telecommunications reforms should be. The Journal welcomes contributions.